Nossa parte da herança. Os frutos de um debate teológico no Brasil - Adão, Francys Silvestrini (Revista eclesiástica brasileira, 2014)
In this article, the author revisits a recent methodological debate among liberation theologians in Brazil. He wonders about the peculiarities of each group’s arguments, as well as about the fundamental issues that such debate provides for the new generation of Brazilian theologians. Through a dialogical and comparative method, the reader is invited to identify what is at stake for the authors in question, highlighting the singularities that legitimately make up the mosaic of the experience of faith and of Christian reflection in this country.